Impulse control difficulties while distressed: A facet of emotion dysregulation links to Non-Suicidal Self-Injury among psychiatric inpatients at military treatment facilities. (November 2018) - Baer, Margaret M.; LaCroix, Jessica M.; Browne, Joy C.; Hassen, Helena O.; Perera, Kanchana U.; Soumoff, Alyssa; Weaver, Jennifer; Ghahramanlou-Holloway, Marjan
Highlights: Military personnel and dependents were assessed following a suicide-related psychiatric admission. Emotion regulation deficits did not link to worse suicide ideation or multiple suicide attempts. Impulse control difficulties differentiated between individuals with and without an NSSI history. Abstract: Links between emotion dysregulation, suicide ideation, and suicidal versus non-suicidal self-injury (NSSI) are poorly understood within military samples. United States service members and beneficiaries ( N = 186), psychiatrically hospitalized following a suicidal crisis, completed the Difficulties in Emotion Regulation Scale (DERS; Gratz & Roemer, 2004), and reported lifetime suicide ideation, attempts, and NSSI. We expected that emotion dysregulation would positively associate with worst lifetime suicide ideation, multiple suicide attempt status, and lifetime NSSI. Suicide ideation severity and multiple suicide attempts did not associate with DERS components. Notably, difficulties with impulse control (feeling out of control while distressed) was positively associated with NSSI history. Theoretical models that clearly describe the role of emotion dysregulation in suicidal thoughts, its progression to suicidal actions, and NSSI are needed to advance clinical care for this highly vulnerable group. Longitudinal and micro-longitudinal study designs require further investigation.